The Phenomenon of Design Thinking of Niqab Fashion Trends Inspiration of Hadith - Yunika Sari; Yeni Huriani (Gunung Djati Conference Series, 2021)
This study aims to discuss the inspiration for the hadith of the Prophet. in the dress code and innovation of the niqab fashion trends. This research method is qualitative through literature and field studies with the hadith design thinking approach. The results and discussion of this research include, the inspiration for the example of the Prophet. in the Niqab dress code and fashion trend innovations. This research concludes that the hadith of the Prophet SAW. has inspirational messages in the phenomenon of fashion trends using "Niqab" through innovative ideas with continuous testing precisely to become a trend that seizes a wide market.